2016
DOI: 10.3847/1538-3881/152/6/226
|View full text |Cite
|
Sign up to set email alerts
|

A Trip to the Cataclysmic Binary Zoo: Detailed Follow-Up of 35 Recently Discovered Systems

Abstract: We report follow-up studies of 35 recently-discovered cataclysmic variables (CVs), 32 of which were found in large, automated synoptic sky surveys. The objects were selected for observational tractability. For 34 of the objects we present mean spectra and spectroscopic orbital periods, and for one more we give an eclipse-based period. Thirty-two of the period determinations are new, and three of these refine published estimates based on superhump periods. The remaining three of our determinations confirm previ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 53 publications
(72 reference statements)
3
20
0
1
Order By: Relevance
“…We reported a weak signal of a possible orbital period of 0.0575060(2) d (vsnet-alert 18017). Thorstensen et al (2016) estimated the orbital period to be 0.05756(6) d from Hα radial velocities via spectroscopy, and they confirmed that this value is consistent with our result. These values are close to the period detected during the outburst of 0.0575054(4) d. The averaged profiles are also similar to each other (the lower panels in figure 2).…”
Section: Orbital Modulationssupporting
confidence: 89%
See 1 more Smart Citation
“…We reported a weak signal of a possible orbital period of 0.0575060(2) d (vsnet-alert 18017). Thorstensen et al (2016) estimated the orbital period to be 0.05756(6) d from Hα radial velocities via spectroscopy, and they confirmed that this value is consistent with our result. These values are close to the period detected during the outburst of 0.0575054(4) d. The averaged profiles are also similar to each other (the lower panels in figure 2).…”
Section: Orbital Modulationssupporting
confidence: 89%
“…They proposed that the decline can be caused by the development of a cavity in the inner disk and that the time scale is about a decade. For another example, Thorstensen et al (2016). SSS J122221.7-311523 (hereafter J1222) showed a fading tail lasting at least 500 d and the brightness just after the superoutburst is about 3 mag brighter (Neustroev et al 2017).…”
Section: Overall Light Curvementioning
confidence: 99%
“…The eclipsing nature was confirmed by Drake et al (2014) and studied later by Thorstensen et al (2016). The highspeed eclipse shows clear white dwarf and bright-spot features.…”
Section: Css090622:215636+193242mentioning
confidence: 71%
“…We report here CV orbital periods measured over the last several decades using the Hiltner 2.4m and McGraw-Hill 1.3m telescopes at MDM Observatory on Kitt Peak, Arizona, mostly with radial-velocity spectroscopy. While most of our results have been published in peer-reviewed articles (see, e.g., Thorstensen et al 2016;Thorstensen & Skinner 2012;Thorstensen et al 2015Thorstensen et al , 2010, many periods we have determined remain unpublished.…”
mentioning
confidence: 99%
“…We report here CV orbital periods measured over the last several decades using the Hiltner 2.4m and McGraw-Hill 1.3m telescopes at MDM Observatory on Kitt Peak, Arizona, mostly with radial-velocity spectroscopy. While most of our results have been published in peer-reviewed articles (see, e.g., Thorstensen et al 2016;Thorstensen & Skinner 2012;Thorstensen et al 2015Thorstensen et al , 2010, many periods we have determined remain unpublished.To make our CV periods available more quickly, and prevent duplication of effort, we present in Table 1 some of our heretofore unpublished P orb s, some of which are refinements of previously-known periods. The instrumentation, observing protocols, reduction, and analysis are described in the papers cited above.…”
mentioning
confidence: 99%